(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Analysis and identification of some factors related to the prevalence of myopia among students at 5 primary schools Vo Thi Sau, Nguyen Thi Minh Khai, Kim Dong Bac Tra My, Kim Dong Tien Phuoc, and Minh Vien in Quảng Nam province in 2023. Subjects and methods: An analytical descriptive study on 1148 second and third-grade students at 5 primary schools above. Results: Results showed that factors associated with refractive errors in primary school students in Quang Nam province included extra classes (OR = 4.761; 95% CI = 2.375-9.543); p < 0.01; inadequate lighting in a learning space (OR = 6.455; 95% CI = 3.454-12.065; p < 0.01); incorrect sitting postures while studying (OR = 2.658; 95% CI = 1.271-5.560; p < 0.01); excessive TV-watching (OR = 4.058; 95% CI = 1.694-9.720; p < 0.01); frequent game playing (OR = 6.910; 95% CI = 3.835-12.451); p < 0.01; housework help (OR = 3.135; 95% CI = 1.602-6.136; p < 0.01); frequent story reading (OR = 3.335; 95% CI = 1.725-6.446; p < 0.01); family history of refractive errors (OR = 4.085; 95% CI = 2.231-7.189; p < 0.01); and a lack of participation in housework (OR = 3.135; 95% CI = 1.602-6.136; p < 0.01). Conclusion: Included extra classes, inadequate lighting in a learning space, incorrect sitting postures while studying, excessive TV-watching, frequent game playing, housework help, frequent story reading, family history of refractive errors and a lack of participation in housework are factors related to refractive errors among primary school students.